LEGAL REVIEW OF VILLAGE CASH LAND RENTAL AGREEMENTS - Akup, Apriliyanto Juwan Sukmana; Rahmatiar, Yuniar; Abas, Muhamad; Sanjaya, Suyono (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
The implementation of leasing village treasury land is a common practice in Indonesia. However, in practice there are legal problems that often arise related to the protection of the rights of the parties involved in it. The implementation of this lease activity is related to the construction of the Subang Smartpolitan Industrial Estate by a private company that has obtained an Industrial Estate Business License (IUKI) in Subang Regency. One of the villages affected by the development of industrial estates has assets in the form of village treasury land that will be changed in function through the ruilslag or exchange process. To regulate the use of land during the ruilslag administrative process, it is considered necessary to first carry out a lease agreement. This legal event highlights the importance of regulating land use changes in a transparent manner and in accordance with applicable regulations. This research uses the Normative Juridical approach method, which is a form of scientific activity, which is based on certain methods, systematics, and thoughts, aiming to study one or several specific legal phenomena. The implementation of the lease agreement for village treasury land is linked to the Regulation of the Minister of Home Affairs Number 3 of 2024 concerning Amendments to the Regulation of the Minister of Home Affairs Number 1 of 2016 concerning Village Asset Management. Several legal aspects that need to be considered in a lease agreement such as Legal Basis, Village Authority, Lease Agreement, Transparency and Openness, Coordination, Protection of Village Rights, Alignment with Development, Supervision and Accountability, Legal Education, Public Supervision. Legal consequences for the parties involved, namely Binding Agreement, Rights and Obligations of the Parties, Duration of Rent, Rent Payment, Land Use, Maintenance and Repair, Transfer of Lease Rights, Sanctions and Fines, Dispute Resolution and Restoration of Village Rights.